P.062 Burden of illness of spinal muscular atrophy (SMA): an update. (June 2019) - Droege, M; Dabbous, O; Arjunji, R; Gauthier-Loiselle, M; Cloutier, M; Sproule, DM
Abstract : Background: In this retrospective claims analysis, real-world healthcare resource use (HRU) and costs among SMA type 1 (SMA1) patients were assessed. Methods: SMA1 patients were identified from Symphony Health's Integrated Dataverse® (09/01/2016–08/31/2018). The study period spanned from the index date (date of first SMA1 diagnosis after nusinersen approval [12/23/2016]) until death/end of available data. HRU and costs per-patient-per-year (PPPY; 2018USD) were described during the study period for all patients and after treatment initiation for nusinersen-treated patients. Results: A total of 349 SMA1 patients (median age=1 year; 55.6% female) with median follow-up of 7.9 months were included. The proportion of patients receiving mechanical ventilation, nutritional support, and physical therapy/rehabilitation was 46.4%, 46.1%, and 22.6%. Patients had, on average, 59.4 days with medical visits/year (14.1 inpatient, 13.4 respiratory failure-related). The 45 nusinersen-treated patients had, on average, 56.6 days with medical visits/year (4.6 inpatient, 11.4 respiratory failure-related). Excluding nusinersen-related costs, mean healthcare costs PPPY were $137, 627 (median: $43, 167) for all patients and $92, 618 ($29, 425) for nusinersen-treated patients. Mean nusinersen-related costs were $191, 909 ($144, 487) per month for the first 3 months post-initiation and $36, 882 ($16, 132) per month thereafter. Conclusions: HRU and costs associated with SMA1 are substantial, even among patients treated with nusinersen.